Migrating Metaphors: Why We Should Be Concerned About a ‘War on Mental Illness’ in the Aftermath of COVID-19 - Sibbald, Kaitlin (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
In the aftermath of the ongoing COVID-19 pandemic, there is a predicted (and emerging) increase in experiences of mental illness. This phenomenon has been described as “the next pandemic”, suggesting that the concepts used to understand and respond to the COVID-19 pandemic are being transferred to conceptualize mental illness. The COVID-19 pandemic was, and continues to be, framed in public media using military metaphors, which can potentially migrate to conceptualizations of mental illness along with pandemic rhetoric. Given that metaphors shape what is considered justifiable action, and how we understand justice, I argue we have a moral responsibility to interrogate who benefits and who is harmed by the language and underlying conceptualizations this rhetoric legitimates. By exploring how military metaphors have been used in the context of COVID-19, I argue that this rhetoric has been used to justify ongoing harm to marginalized groups while further entrenching established systems of power. Given this history, I present what it may look like were military metaphors used to conceptualize a “mental illness pandemic”, what actions this might legitimate and render inconceivable, and who is likely to benefit and be harmed by such rhetorically justified actions.